Influence of fermentation temperature and source of enzymes on enological characteristics of rice wine. Issue 3 (14th April 2014) - Liu, Dengfeng; Zhang, Hongtao; Xu, Baoguo; Tan, Jinglu
<x xml:space="preserve">Abstract</x> Rice wine samples were produced with four sources of enzymes, and with three fermentation temperatures. Key enological variables (including ethanol, the main sugars, glycerol and organic acids) were measured by HPLC at the end of primary fermentation (4 days) and at the end of the postfermentation period (40 days). The results showed that both source of enzymes and temperature had significant effects on the main flavour compounds. Ethanol varied initially, but its final concentration showed a weak dependence on the treatments. Faster starch hydrolysis led to higher initial sugar concentrations, but lower final sugar and higher final glycerol concentrations. Production of organic acids, lactic acid and acetic acid, in particular, depended on the fermentation temperature. The results provide insights into the rice wine fermentation process as affected by different enzymes and fermentation temperatures. Copyright © 2014 The Institute of Brewing & Distilling